カムチャツカ半島北部の火成活動とテクトニクス - 西澤達治; Tatsuji Nishizawa (2018)
The relationship between the tectonic setting and arc magmatism is discussed for the northern Kamchatka Peninsula corresponding to the subduction of the northwestern edge of the Pacific Plate. First, on the basis of genetic conditions of the high-Mg andesite including ultra-high-Ni olivine and the primitive basaltic lavas that erupted in the forearc area, chemical and thermal effects of a subducting seamount are inferred to have caused temporal and local magmatism with a wide compositional range. Second, field work, age dating and geochemical analysis for the lavas in the northern Sredinny Range have revealed that Quaternary magmatism exists beyond the slab edge of the Pacific Plate, yet shows influences from subducted slab materials. Based on these results, a new tectonic and mantle dynamic model is proposed for origin of the magmatism.